2016
DOI: 10.1055/s-0042-101546
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Associated Anxiety among Pregnant Women and their Partners: What is the Influence of Sex, Parity, Age and Education?

Abstract: Pregnancy is an extraordinary time for every woman and it is experienced very differently by each individual. It is generally associated with incalculable risks, such as fetal malformations or maternal illnesses that may affect the child. These dangers cause manifestations of anxiety not only in pregnant women but also in their partners, the expectant fathers. Abstract !Background: Anxiety during pregnancy can influence outcomes negatively. The aim of this study was to assess the fears of expectant parents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 11 publications
1
22
1
Order By: Relevance
“…Regarding the association with contextual factors, a negative bivariate correlation with paternal age showed that younger fathers reported higher pregnancy-related worries, which is in line with previous literature (63,74). However, in multiple regression analysis, paternal age did not significantly explain variance in pregnancy-related worries.…”
Section: Associations With the Included Variablessupporting
confidence: 88%
See 3 more Smart Citations
“…Regarding the association with contextual factors, a negative bivariate correlation with paternal age showed that younger fathers reported higher pregnancy-related worries, which is in line with previous literature (63,74). However, in multiple regression analysis, paternal age did not significantly explain variance in pregnancy-related worries.…”
Section: Associations With the Included Variablessupporting
confidence: 88%
“…This might lead to higher pressure in fathers and be reflected in the stronger concerns related to financial aspects compared to the maternal sample of Petersen et al (76). However, in another German study, not being able to provide financially for the child was among the lower concerns not only in mothers but also in fathers (74). One explanation for these divergent results could be that not having enough financial resources to cover specific expenses related to childcare might not be a relevant cause for concern, but the overall financial situation due to these expanses along with a reduced household income due to pregnancy and maternity leave might be.…”
Section: Distribution Of Concernsmentioning
confidence: 90%
See 2 more Smart Citations
“…Prenatal diagnosis of a fetus brain abnormality will increase the pressure on parents, not only diagnostic uncertainties in some cases but also unclear of information on the long‐term outcome. Some studies have suggested that increased anxiety and continuing stress in pregnant women may lead to developmental delay and decreased coping ability after childbirth . Shengli Li et al .…”
Section: Discussionmentioning
confidence: 99%